2021
DOI: 10.3389/fcvm.2021.758158
|View full text |Cite
|
Sign up to set email alerts
|

Activated Protein C Ameliorates Diabetic Cardiomyopathy via Modulating OTUB1/YB-1/MEF2B Axis

Abstract: Graphical AbstractIn mouse model of chronic diabetes mellitus, persistent hyperglycemia impaired thrombin-thrombomodulin-EPCR dependent PC activation. The reduced aPC-dependent cytoprotective signaling via PAR1/EPCR supressed OTUB1 expression resulting in augmented K48 ubiquitination and proteasomal degradation of the transcription factor YB-1. Within the nucleus, YB-1 binds to MEF2B promoter and restrains its transcription. Accordingly, ubiquitination and reduced protein levels of YB-1 compromised its inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Recently, we showed that the YB-1 acts as a transcriptional suppressor, which binds directly to the promoter region of another important cardiomyopathy-related transcriptional factor myocyte enhancer factor 2B and suppresses its expression. Hyperglycemia caused proteasome-dependent YB-1 protein degradation results in myocyte enhancer factor 2B overexpression, which contributes to the development and formation of DCM (43).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that the YB-1 acts as a transcriptional suppressor, which binds directly to the promoter region of another important cardiomyopathy-related transcriptional factor myocyte enhancer factor 2B and suppresses its expression. Hyperglycemia caused proteasome-dependent YB-1 protein degradation results in myocyte enhancer factor 2B overexpression, which contributes to the development and formation of DCM (43).…”
Section: Discussionmentioning
confidence: 99%
“…The DCM model was implemented by placing mice on a high-fat (D12492, Research Diet) diet for 4 weeks, followed by overnight fasting and intraperitoneal injection with a dose of streptozotocin (STZ) (50 mg/kg × 5 days) dissolved in pH 4.5 sodium citrate buffer. After one week, mice with blood glucose higher than 16.7 mmol/L were considered as having DM [ 23 ] and continuous high-fat feeding. Control mice were given a normal diet and treated with sodium citrate buffer and continuous normal diet feeding.…”
Section: Methodsmentioning
confidence: 99%
“…These indicate that APC activates the activity of ERK1/2 to suppress apoptosis in IMN, and the inhibition of ERK1/2 activity has an impact on the blocking effect of APC on apoptosis. Recent study has shown that APC can promote YB-1 translocating into the nucleus through ERK1/2 activation [18,27]. The results of WB showed that YB-1 had obvious entry into the nucleus in the APC-treated IMN cell model.…”
Section: Erk1/2 Ameliorates Imn By Promoting Yb-1 Entry Into the Nucl...mentioning
confidence: 89%
“…Recent studies have identified the anti-inflammatory effects of APC in vascular endothelial cells, and APC is involved in regulatory crosstalk of EPCR, ERK, and NF-κB, thereby disrupting TNF signaling [17]. Further, previous data suggest that APC through PAR1/EPCR signaling maintain YB-1 levels by preventing YB-1 ubiquitination through OTUB1 [18,27]. Here, adding APC to IMN cells can increase the phosphorylation of ERK1/2 and promote the translocation of YB-1 to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation